10.3928/08910162-20080701-01 (CrossRef Listing of Deleted DOIs, 2000)
Background Transgender and gender-diverse (TGD) individuals experience stigma and discrimination that contribute to health inequities. Many health care providers receive limited education on TGD-specific care. This study evaluated the impact of a trauma-informed digital storytelling (DST) continuing education (CE) module on health care professionals' attitudes, beliefs, and comfort regarding the care of TGD individuals. Method A single-group pre-post study design was conducted with clinicians and allied health staff in a regional health system (n = 154). Participants completed the Transgender Attitudes and Beliefs Scale (TABS) before and after a 1-hour asynchronous module featuring digital stories from TGD individuals and a parent of a TGD child, plus open-ended reflections. Results Statistically significant improvements were observed in Interpersonal Conflict (median increase = 2.5), Sex/Gender Beliefs (median increase = 2.0), and total TABS scores (median increase = 4.5; all p < .001). Conclusion Trauma-informed DST-based CE is feasible and may promote reflective learning and more inclusive attitudes toward TGD patient care.